MHD Mixed Convection Jeffrey Fluid Near a Stagnation-Point Flow of Induced Magnetic Field and Linear/Non-Linear Vertical Stretching Sheet with Chemical Reaction in The Presence of Thermal Radiation and Suction or Injection - et. al., G.Kathyayani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The effect of induced magnetic field and chemical reaction with linear / non-linear vertical stretching sheet of mixed convection Jeffrey fluid near a stagnation point flow through porous medium in the presence of thermal radiation and slip flow regime is analyzed. The set of coupled governing non-linear partial differential equations are transformed into a set of coupled non-linear ordinary differential equations using suitable similarity transformations, which are then solved numerically using Runge-Kutta fourth order in association with shooting technique in MATLAB. The effects of non-dimensional parameters such as Jeffrey parameter, Magnetic force number, magnetic Prandtl number, magnetic parameter, suction/injection parameter, slip velocity parameter, linear or non-linearity parameter, permeability parameter, velocity ratio parameter, Prandtl number, thermal radiation parameter, chemical reaction parameter, Grashof number and Eckert number on velocity, temperature induced magnetic field and concentration are presented graphically while the skin friction, local Nusselt number and Sherwood number are represented numerically with tables.